Cysticercal encephalitis with disseminated cutaneous cysticercosis: A case report - Verma, Parul; Verma, Nishant (Indian Journal of Child Health, 2015)
Cysticercal encephalitis is a severe and frequently fatal neurological disorder seen in endemic regions. We report a young male who presented with refractory status epilepticus along with numerous subcutaneous swellings over the body. His neuroimaging revealed the classic “starry sky” appearance, suggesting a diagnosis of cysticercal encephalitis along with disseminated cutaneous cysticercosis. He was managed with supportive care, antiepileptics and steroids. In endemic regions, neurocysticercosis should be considered as a differential diagnosis in children presenting as acute encephalitis syndrome. A careful physical examination along with early neuroimaging will help in establishing the diagnosis promptly.